1988
DOI: 10.1038/eye.1988.130
|View full text |Cite
|
Sign up to set email alerts
|

Post-keratoplasty glaucoma

Abstract: SummaryThe incidence of post-keratoplasty glaucoma remains at about 30% of all grafts performed.Aphakic eyes, particularly those after intracapsular extraction, the elderly, traumatised eyes and eyes undergoing repeat corneal grafts appear to be at greatest risk. This paper also reviews the mechanisms and treatment of post keratoplasty glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 25 publications
2
39
2
2
Order By: Relevance
“…The reported incidence of secondary glaucoma after PKP ranges 10-53%. [33][34][35][36][37] One subject (7.1%, Patient 13) suffered from secondary glaucoma with painful red eye and no light perception and received evisceration at 39 month follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…The reported incidence of secondary glaucoma after PKP ranges 10-53%. [33][34][35][36][37] One subject (7.1%, Patient 13) suffered from secondary glaucoma with painful red eye and no light perception and received evisceration at 39 month follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies found a high correlation between PAS and IOP elevation after PK and post-PK glaucoma [7,16,17,18,19,20,21,22]. After DSEK, steroid-related ocular IOP elevation was identified as a major cause [1,13].…”
Section: Introductionmentioning
confidence: 99%
“…Durable uncontrolled elevation of IOP and manifest post-keratoplasty glaucoma are major risk factors for poor visual outcome, endothelial cell loss and subsequent graft failure after keratoplasty. After penetrating keratoplasty (PK), an increasing incidence of IOP elevation from 29 to 80% was reported [1,2,3,4,5,6,7]. Post-PK glaucoma occurred in 9-35% of cases [2,6,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The incidence of glaucoma after keratoplasty varies from 9% to 31% in the early postoperative period and from 18 to 35% in the late postoperative period. 4,5 The aetiology of this disorder is multifactorial and the clear understanding of the various mechanisms that operate during different time frames following penetrating keratoplasty is essential to chalk out the appropriate management algorithms.…”
Section: Introductionmentioning
confidence: 99%